Indonesian learners’ perception on the usage of mobile applications in writing skill - Mega Indah Mutiarasari; N Ngadiso; Diah Kristina (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2020)
Nowadays, digital technologies play significant roles in daily life. In educational context, these technologies help learners to gain more knowledge. However, the learners mainly use mobile devices for non-academic purposes, like play game or open the social media applications rather than use the learning applications. In fact, mobile device is an effective media that can make the learners motivated and more interested in learning English. The further research needs to investigate students’ perception on the usage of mobile applications especially in creative writing skill. The participants of the research are 30 senior high school students consisting of 12 males and 18 females. The data is collected by using close-ended questionnaire. This research classified as case study research using randomized sampling. Descriptive data analysis was conducted. The results indicate that mobile applications generally give some advantages in learning English. The perceived benefits of mobile learning comprised opportunities to have ubiquitous learning, have so many exercises, analyze the specific mistakes the learner has made, and also explain the principles behind the correct answer. The learners should maximize the usage of mobile applications positively. The findings have several significant implications for educators, particularly for the use of mobile applications in academic purposes and the strategies to implement mobile learning.